2013
DOI: 10.1016/j.bbadis.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Balanced translocation t(3;18)(p13;q22.3) and points mutation in the ZNF407 gene detected in patients with both moderate non-syndromic intellectual disability and autism

Abstract: Intellectual disability (ID) is a common disease. While the etiology remains incompletely understood, genetic defects are a major contributor, which include mutations in genes encoding zinc finger proteins. These proteins modulate gene expression via binding to DNA. Consistent with this knowledge, we report here the identification of mutations in the ZNF407 gene in ID/autistic patients. In our study of an ID patient with autism, a reciprocal translocation 46,XY,t(3;18)(p13;q22.3) was detected. By using FISH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Moreover, it was reported that missense mutations in ZNF407 affect tumor progression, as evidenced by whole-genome sequencing of gastrointestinal stromal tumors. 28 Moreover, our functional studies of ZNF407 showed that ZNF407 functioned as a promotive factor in CRC metastasis and accelerated cell proliferation slightly (Supplementary Figure S3). Together, these data suggest a novel theory that CRC metastasis is regulated by WDR5.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, it was reported that missense mutations in ZNF407 affect tumor progression, as evidenced by whole-genome sequencing of gastrointestinal stromal tumors. 28 Moreover, our functional studies of ZNF407 showed that ZNF407 functioned as a promotive factor in CRC metastasis and accelerated cell proliferation slightly (Supplementary Figure S3). Together, these data suggest a novel theory that CRC metastasis is regulated by WDR5.…”
Section: Discussionmentioning
confidence: 92%
“…More importantly, molecular studies revealed that WDR5-transfected cells underwent EMT and were modulated by the PI3K/AKT signaling pathway. Furthermore, gene expression microarrays were used to identify ZNF407, which was reported to affect tumor progression, 27, 28 as a novel target of WDR5, which markedly increased CRC cell migration. Thus, we propose that WDR5 is a promising target in CRC prognostics and therapeutics.…”
mentioning
confidence: 99%
“…Aural atresia is caused by hemizygosity of the TSHZ1 gene (Feenstra et al, 2011). Hemizygosity of several genes have been implicated in cognitive abilities, ZNF407 (Ren et al, 2013) and NETO1 (Ng et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Analysis of several CAA patients led to defining the breakpoint of the deletion within ZNF407 [24] . Another identified translocation breakpoint in the third intron of the ZNF407 gene causes a reduction in the transcript of its isoform 1, resulting in non-syndromic intellectual impairment and autism [25]. Furthermore, two de novo damaging missense mutations [c.A1436G/p.Y460C; c.C3640G/p.P1195A] in the very long linker region between zinc fingers 3 and 4, and between 11 and 12, respectively, of the ZNF407 gene were found in one intellectual impairment patient each.…”
Section: Discussionmentioning
confidence: 99%